Effective diabetes complication management is a step toward a carbon-efficient planet: an economic modeling study. Issue 1 (16th April 2020) - Fordham, Ric; Dhatariya, Ketan; Stancliffe, Rachel; Lloyd, Adam; Chatterjee, Mou; Mathew, Mevin; Taneja, Loveleen; Gains, Mike; Haagen Panton, Ulrik
Abstract : Background: The management of diabetes-related complications accounts for a large share of total carbon dioxide equivalent (CO2 e) emissions. We assessed whether improving diabetes control in people with type 2 diabetes reduces CO2 e emissions, compared with those with unchanging glycemic control. Methods: Using the IQVIA Core Diabetes Model, we estimated the impact of maintaining glycated hemoglobin (HbA1c ) at 7% (53 mmol/mol) or reducing it by 1% (11 mmol/mol) on total CO2 e/patient and CO2 e/life-year (LY). Two different cohorts were investigated: those on first-line medical therapy (cohort 1) and those on third-line therapy (cohort 2). CO2 e was estimated using cost inputs converted to carbon inputs using the UK National Health Service's carbon intensity factor. The model was run over a 50-year time horizon, discounting total costs and quality adjusted life years (QALYs) up to 5% and CO2 e at 0%. Results: Maintaining HbA1c at 7% (53 mmol/mol) reduced total CO2 e/patient by 18% (1546 kgCO2 e/patient) vs 13% (937 kgCO2 e/patient) in cohorts 1 and 2, respectively, and led to a reduction in CO2 e/LY gain of 15%–20%. Reducing HbA1c by 1% (11 mmol/mol) caused a 12% (cohort 1) and 9% (cohort 2) reduction in CO2 e/patient with a CO2 e/LY gain reduction of 11%–14%. Conclusions: When comparing people with untreated diabetes, maintaining glycemic control at 7% (53 mmol/mol) on a single agent or improving HbA1c by 1% (11 mmol/mol) by the addition of more glucose-lowering treatment was associated with a reduction in carbon emissions.